ACE2‐Variants Indicate Potential SARS‐CoV‐2‐Susceptibility in Animals: A Molecular Dynamics Study. Issue 9 (10th August 2021) - Pach, Szymon; Nguyen, Trung Ngoc; Trimpert, Jakob; Kunec, Dusan; Osterrieder, Nikolaus; Wolber, Gerhard
Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS‐CoV‐2) continues to be a global threat, causing millions of deaths worldwide. SARS‐CoV‐2 is an enveloped virus with spike (S) glycoproteins conferring binding to the host cell's angiotensin‐converting enzyme 2 (ACE2), which is critical for cellular entry. The host range of the virus extends well beyond humans and non‐human primates. Natural and experimental infections have confirmed the high susceptibility of cats, ferrets, and Syrian hamsters, whereas dogs, mice, rats, pigs, and chickens are refractory to SARS‐CoV‐2 infection. To investigate the underlying reason for the variable susceptibility observed in different species, we have developed molecular descriptors to efficiently analyse dynamic simulation models of complexes between SARS‐CoV‐2 S and ACE2. Our extensive analyses represent the first systematic structure‐based approach that allows predictions of species susceptibility to SARS‐CoV‐2 infection. Abstract :